The Walking Qur’an: Islamic Education, Embodied Knowledge, and History in West Africa By Rudolph Ware III (Chapel Hill: University of North Carolina Press, 2014. 330 pages.) (American Journal of Islam and Society, 2015)
With the introduction of new educational systems in the Muslim world duringthe late-eighteenth through the early-twentieth century, many Muslims andnon-Muslims became critical of traditional pedagogical methods. In particular,the image of Qur’an schools in West Africa are often criticized for their“backward” forms of education and commonly perceived as places wherechildren simply parrot Qur’anic verses without much understanding. Theseinstitutions have largely been abandoned and replaced by modern and secularschooling systems. In his The Walking Qur’an, Rudolph Ware argues thatQur’an schools have survived in places like West Africa. By studying them,he seeks to historicize this once-paradigmatic approach to knowledge. Alongwith shedding light on Islamic knowledge, Ware attempts to move beyondrace by placing Africans at the center of Islamic studies. Such an attempt is welcome, given the rarity of in-depth studies on Islamic history in WestAfrica. In so doing he makes a welcome contribution to both Islamic andAfrican studies, while simultaneously examining the boundaries between thetwo ...